“They are all here to see and touch”: Materiality, Religious Mixing and Post-communism: St Anthony’s Pilgrimage in Laç - Bria, Gianfranco; Giorda, Maria Chiara (Fieldwork in Religion, 2024)
The sanctuary of St Anthony of Padua (Kisha e Shna Ndout) in Laç, northern Albania, is one of the most visited religious places in Albania. The small church, built there and ministered by Franciscans, is now an impressive place of worship frequented by Catholics, Muslims and Christian Orthodox. Throughout the year, pilgrims from across the country, but also from Kosovo, visit the sanctuary. On the 12th and 13th of June of each year, an official pilgrimage is held, which reaches its climax on the night of the 12th when many thousands of Albanians sleep in the shrine seeking blessings and healing. This article aims to explore pilgrimage-related practices, wherein arises materiality as a privileged means of reaching out to the divine and as a reaction to silencing during the communist era (1945–1991). Such practices are overshadowed by nationalist discourse, in which ethnic-linguistic membership outweighs the religious one, even undermining procedural and terminological normativity.